THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND SPEAKING ABILITY OF THE 8TH GRADE STUDENTS IN SMP IT CAHAYA HATI BUKITTINGGI - Opida Nengsih; Melyann Melani; Reflinda Reflinda; Irwandi Irwandi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to analyse the relationship between students' motivation and their speaking ability in English. The study was conducted on 42 grade VIII students at SMP IT Cahaya Hati Bukittinggi. Students' motivation was measured through a questionnaire, while speaking ability was assessed using a speaking test. The data was analysed using Pearson Correlation Formula, which showed a significant positive correlation with a value of 0.739. These results show that the higher the students' motivation, the better their speaking ability. However, there were also some unique cases where students with high motivation still had difficulty speaking, while some students with low motivation were able to speak well. This finding confirms that besides motivation, other factors such as learning methods and learning environment also affect speaking ability. Therefore, teachers need to create a supportive learning environment and provide effective strategies to improve students' motivation as well as speaking skills in English.